2022
DOI: 10.3389/fneur.2022.924057
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and adverse reactions of perampanel in the treatment of epilepsy in children

Abstract: ObjectiveTo observe the clinical effect and adverse reactions of perampanel in the treatment of epilepsy in children.MethodsA retrospective analysis was performed on 83 children with epilepsy who were treated with perampanel in the Department of Pediatric Neurology, Second Affiliated Hospital of Xi'an Jiaotong University from April to August 2021. The treatment status, prognosis and adverse reactions were followed up. The effective rates of different age groups, different seizure types and epilepsy syndromes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The above results suggested that PER monotherapy had generalizability for focal epilepsy with a variety of etiologies in children. In addition, PER monotherapy had higher effective rates for SeLECTs, SeLEAS, and COVE, all of which were more than 80% in our study, which was similar to the previous studies ( 12 ). The lower effective rate of SHE was not discussed because of the small number of cases.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The above results suggested that PER monotherapy had generalizability for focal epilepsy with a variety of etiologies in children. In addition, PER monotherapy had higher effective rates for SeLECTs, SeLEAS, and COVE, all of which were more than 80% in our study, which was similar to the previous studies ( 12 ). The lower effective rate of SHE was not discussed because of the small number of cases.…”
Section: Discussionsupporting
confidence: 92%
“…Future studies need large samples to confirm the effectiveness of PER monotherapy for focal epilepsy in children. Other epilepsy syndromes shown in previous studies, such as Dravet syndrome ( 8 , 12 , 13 ), Lennox–Gastaut syndrome ( 18 20 ), and focal epilepsy combined with ESES ( 10 ), presented good effectiveness with PER treatment.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…1,2,[14][15][16] Several studies reported perampanel monotherapy was effective and safe in treating adult and pediatric patients with refractory FOS with or without FBTCS, and most of these studies were retrospective studies. [17][18][19][20][21][22] In China, except for one retrospective study that reported perampanel monotherapy was efficacious and safe in eight of the nine treated pediatric patients with epilepsy, 23 there has been no other published study on the efficacy and safety of perampanel monotherapy in treating FOS. In China, perampanel is currently most used as adjunctive therapy in treating patients with epilepsy as experience in utilizing it for monotherapy is lacking.…”
Section: Introductionmentioning
confidence: 99%